English Games Untuk Meningkatkan Speaking Skill Dan Motivasi Siswa Kelas X SMK - Nurbadri Nurbadri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
Teaching speaking should be oriented to the vocational purpose at SMK. In reality, many students get problem to speak English and get low learning motivation. This makes them unsuccessful to get the proper jobs. The purpose of this research was to test whether the game can improve students’ speaking skill and their learning motivation at grade one of SMK Negeri 2 Sawahlunto and to find out factors influence the improvement the speaking skill and learning motivation. This research is classified into classroom action research. Data were collected through assessment, observation, and interview. The assessment was used for assessing the speaking; the observation sheet was used for assessing students’ learning motivation and then interview and field note were used for having the further information. The findings of this research have answered the research questions, that the using English game can improve students’ speaking skill and learning motivation at SMKN 2 Sawahlunto. This technique is very useful to improve students’ speaking skill and learning motivation. This technique must be applied at SMKN 2 Sawahlunto, and it is suggested that school with poor speaking skill and low learning motivation to apply and develop this method to overcome their learning English problem.